LEFT VENTRICULAR ROTATION, TWIST AND UNTWIST: PHYSIOLOGICAL ROLE AND CLINICAL RELEVANCE - E. N. Pavlyukova; D. A. Kuzhel; G. V. Matyushin; E. A. Savchenko; S. A. Filippova (Рациональная фармакотерапия в кардиологии)
The helical ventricular myocardial band of Torrent-Guasp is a new concept, which provides strong grounds for reconciliation of some important aspects in cardiovascular medicine. Oblique fiber orientation provides left ventricular rotation, which in addition to radial thickening and longitudinal shortening, is predicted as an essential component of the effective left ventricular pumping. Left ventricular rotation can be measured in clinical practice noninvasively using echocardiography and this provides new opportunities for the assessment of different aspects of left ventricular mechanical function.